The Effects of Ketamin-Midazolam and Ketamin-Propofol on Bispectral Index Score as Sedatives During Bone Marrow Puncture Procedure Among Pediatrics - Aldiar; Fredi Heru Irwanto; Andi Miarta; Irfannuddin (Journal of Anesthesiology and Clinical Research, 2021)
Background: Bone Marrow Puncture (BMP) is an invasive procedure associated with pain and anxiety. The ketamine-midazolam and the ketamine-propofol is an effectivecombination with minimal side effects. This study of the study aims to compare the effect of the combination of ketamine-midazolam and ketamine- propofol on sedation depth based on BIS in pediatric leukemia patients undergoing BMP. Methods: This study was a randomized controlled trial that was done single-blinded. The population was all pediatric patients diagnosed with leukemia who underwent BMP at RSMH and performed sedation. The research sample is the population that fulfill the inclusion and exclusion criteria. The sample size for each group was 25, with 50 Subjects in total. Sampling was done by block randomization. Results: This study found no differences in sex, age, and body weight between the two groups ([p=1.000], [p=0.845], and [p=0.147], respectively). In this study, there was no difference in mean MAP (p=0.592), oxygen saturation (p=0.164), heart rate (p=0.098), and respiratory rate (p=0.252) before intervention between the two groups. BIS value of the two groups had significant difference before and after the intervention where the two groups could reduce BIS to reach the optimal value of sedation <60 (p <0.05) There was no difference in BIS before intervention in the two groups (p=0.385). In this study, it was found that hypersalivation occurred more frequently in the ketamine-midazolam combination group. Conclusion: The combination of ketamine-midazolam and ketamine-propofol was equally good for sedation as indicated by a decrease in the mean BIS in patients undergoing BMP.